'Jumper' managers' vulnerable involvement/avoidance and trust/distrust spirals. Issue 2 (3rd July 2019) - Shapira, Reuven
ABSTRACT: Earlier ascending/descending trust spirals have been explained by the job discretion allowed to employees by managers; few have studied such spirals as this has required a bi-directional longitudinal framework. Such a framework has used ethnographies of managers who 'jumped' from other organisations and suffered gaps of knowledge that curbed their psychological safety. Gap-exposing vulnerable involvement in locals' deliberations would have been required for mutual trust building. These managers were mostly detached or autocratic and generated descending trust spirals which barred locals' knowledge-sharing. In their ignorance they used immoral subterfuge, furthered distrust, shaped low-trust cultures, and mismanaged. However, detached/autocratic 'jumpers' often managed mediocrely by 'riding' on the successes of trusted vulnerably involved mid-levelers. Only a few 'jumpers' generated ascending mutual trust spirals by vulnerable involvement, learned from and with locals, and succeeded by shaping high-trust innovation-prone cultures. Contextual factors helped explain choices of practicing/avoiding vulnerable involvement and generating ascending/ descending trust spirals. Further study of these choices and these factors is suggested.